2003
DOI: 10.1142/s0217979203019083
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Deformation Behavior of Rubber under High Strain Rate Compressive Loading

Abstract: A specific experimental method, the split Hopkinson pressure bar (SHPB) technique is used to determine the dynamic material properties under the impact compressive loading condition with strain-rate of the order of 10 3 /s~10 4 /s. The dynamic deformation behavior of rubber materials widely used for the isolation of vibration from varying structures under dynamic loading is determined by using the Split Hopkinson Pressure Bar technique. The relationships between the stresses at transition points of rubber mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Through the range of strain rates tested, the silicones exhibit a significant strain rate dependency whereby at higher strain rates the silicones experience a more pronounced strain hardening effect; this was more apparent in the stiffer contracted muscle simulant. This behaviour is consistent with results from literature (Gray III et al, 1997;Lee et al, 2003;Kakavas, 1996;Jones, 1960). Gray III et al (1997) conducted uniaxial compressive tests on silicone rubbers and noted that the Young's modulus increased by a factor of 8 when strain rate was increased from 10 -3 to 3×10 3 s -1 , whilst little change was observed between strain rates 10 -3 -10 -1 s -1 .…”
Section: Silicone Behavioursupporting
confidence: 91%
“…Through the range of strain rates tested, the silicones exhibit a significant strain rate dependency whereby at higher strain rates the silicones experience a more pronounced strain hardening effect; this was more apparent in the stiffer contracted muscle simulant. This behaviour is consistent with results from literature (Gray III et al, 1997;Lee et al, 2003;Kakavas, 1996;Jones, 1960). Gray III et al (1997) conducted uniaxial compressive tests on silicone rubbers and noted that the Young's modulus increased by a factor of 8 when strain rate was increased from 10 -3 to 3×10 3 s -1 , whilst little change was observed between strain rates 10 -3 -10 -1 s -1 .…”
Section: Silicone Behavioursupporting
confidence: 91%
“…Bergström and Boyce [23] tested the compressive properties of nitrile and chloroprene rubber and found that the compressive tangent modulus at a true strain of 0.45 increased by approximately 10 % with the strain rate increase from 2 • 10 -4 to 10 -1 s -1 . And Lee et al [24] found, for three unspecified rubber materials, the compressive tangent modulus increased by 400 % with the strain rate increase from 1 to 5 • 10 3 s -1 . The above test data, both ours and the previous, show that the rate effect is not significant at low strain rates (generally below 1 s -1 ), but it becomes very strong when the strain rate ranges from low level to high level (of order 10 3 s -1 ), at least for some rubbers.…”
mentioning
confidence: 93%
“…Zhao Xijin et al [13] investigated the dynamic compressive behaviors of a silicon rubber at high strain rates by applying quartz crystal. Lee O. S. et al [14] analyzed the dynamic deformation of rubber by using the SHPB technique, and found that the relationships between the stresses and the strain rates at the transition point are found to be bilinear. Doman D. A. et al [15] performed the high-rate, uniaxial compression tests using a Polymeric SHPB, and studied the effectiveness of both the modified quasi-linear viscoelastic model and the non-linear hyper-viscoelastic model to describe the low-rate and high-rate behavior of polyurethane rubber.…”
Section: Introductionmentioning
confidence: 99%